The effect of fiscal drag on income distribution and work incentives: A microsimulation analysis on selected African countries - Adnan Abdulaziz Shahir; Francesco Figari (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Although the effect of fiscal drag is well studied in the industrialized world, empirical evidence from developing economies remains limited. Against this backdrop, this study aims to explore the effect of fiscal drag on income distribution and work incentives. To this end, the study employs SOUTHMOD, the tax-benefit microsimulation model, for six African countries: Ethiopia, South Africa, Tanzania, Uganda, Mozambique, and Zambia. Three important conclusions are drawn from our empirical investigation. First, in the absence of proper tax parameter adjustment, the distribution of fiscal drag is determined by the liability progression of personal income tax in the pre-inflation period. Second, the impact of fiscal drag on the redistributive effects and progressivity of personal income taxes is differentiated among countries. On the one hand, it reduces the progressivity of personal income tax in Ethiopia, South Africa, Tanzania, Uganda, and Zambia; on the other hand, it improves progressivity in Mozambique. However, it decreases the redistributive effect of personal income tax only in Ethiopia, Tanzania, and Uganda. Third, fiscal drag reduces financial work incentives to increase earnings in all countries. Therefore, a comprehensive and frequent inflationary adjustment of tax parameters to circumvent fiscal drag would be welcome.
Keywords: C81; D31; H24; 330; inflation; income tax; fiscal drag; redistributive effects; Africa; microsimulation